2023
DOI: 10.3390/pharmaceutics15031009
|View full text |Cite
|
Sign up to set email alerts
|

DLin-MC3-Containing mRNA Lipid Nanoparticles Induce an Antibody Th2-Biased Immune Response Polarization in a Delivery Route-Dependent Manner in Mice

Abstract: mRNA-based vaccines have made a leap forward since the SARS-CoV-2 pandemic and are currently used to develop anti-infectious therapies. If the selection of a delivery system and an optimized mRNA sequence are two key factors to reach in vivo efficacy, the optimal administration route for those vaccines remains unclear. We investigated the influence of lipid components and immunization route regarding the intensity and quality of humoral immune responses in mice. The immunogenicity of HIV-p55Gag encoded mRNA en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…This observation was made during the comparison between LM1-LNP (ALC-0315) and LM4-LNP (DLin-MC3-DMA), where the substitution of ALC-0315 with Dlin, an immunogenic ionizable lipid, led to reduced mRNA expression. This heightened reactogenicity was consistent with our measurements of cytokine secretion as well [ 29 ]. In another scenario, the replacement of the helper DSPC lipid with DOPE (in LM1 and LM2, respectively) may lead to differences in expression and biodistribution after intramuscular injection.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation was made during the comparison between LM1-LNP (ALC-0315) and LM4-LNP (DLin-MC3-DMA), where the substitution of ALC-0315 with Dlin, an immunogenic ionizable lipid, led to reduced mRNA expression. This heightened reactogenicity was consistent with our measurements of cytokine secretion as well [ 29 ]. In another scenario, the replacement of the helper DSPC lipid with DOPE (in LM1 and LM2, respectively) may lead to differences in expression and biodistribution after intramuscular injection.…”
Section: Resultssupporting
confidence: 92%
“…The mRNA for mouse administration was around 7 µg, which was higher than other reports (4 µg/mice [ 8 ]; 3 µg/mice [ 29 ]), but well under other doses tested for metabolic diseases: 20 µg/mice for hereditary tyrosinemia 1 [ 5 ], 60 μg/mice for phenylketonuria [ 6 ], or the 10 µg/mice doses used in LNP inflammation studies [ 30 ]. Similarly to the approach with PBMCs, high doses of mRNA may be related to high doses of lipids, which represents a suitable situation to study the effect of the lipids on the immune response.…”
Section: Resultsmentioning
confidence: 71%
“…Although COVID-19 vaccines are administered intramuscularly 10 , Friedensohn et al found a higher seroconversion rate with accidental subcutaneous administration 340 . This is in line with the study by Yavuz et al, who observed ionizable LNPs induced Ab Th2-biased immunity when subcutaneously administered 70 . Direct intramuscular and intradermal injections of LNP-mRNA were shown to offer the best levels of antigen expression and duration of effect, with the production of antigen protein peak at 4 hours, and maintained locally 8-10 days after injection, depending on the dose.…”
Section: Variation In Adverse Eventssupporting
confidence: 93%
“…Therefore, ionizable cationic lipids are deprotonated under neutral conditions and positively charged under low pH conditions, thus below the acid dissociation constant (pKa) of the lipid [66][67][68][69] . The LNPs used in the Pfizer and Moderna COVID-19 vaccines contain an ionizable lipid, a structural phospholipid, cholesterol, and a PEG-lipid in molar ratio 70 . The ionizable lipid used in the Pfizer vaccine is ALC-0315, while SM-102 was used in the Moderna vaccine 71 .…”
Section: Safety Concernsmentioning
confidence: 99%
See 1 more Smart Citation